Quasi‐experimental quantitative study of training programme for nurses and midwives regarding provision of neonatal resuscitation in selected governmental hospital, (Sudan), 2018 - Namarig Nasraldin Gidam; Widad Ibrahim Abdelgair (Nursing Open, 2023)
Abstract Aims To measure the effectiveness of educational programmes for nurses regarding knowledge and practice of advanced resuscitation for newborn infants. Design This is a quasi‐experimental study in (Sudan, White Nile state), to evaluate the effectiveness of designed guidelines regarding advanced neonatal resuscitation for midwives during the period November 2020–January 2021. Methods Data were collected using two tools: semi‐structured questionnaire and checklist. The number of the respondents to the questionnaire is 75 nurses. Statistical analyses were conducted using SPSS (version 22). Data were expressed as percentages. The results show that the level of knowledge is improved significantly after training programme interventions, with safe practice reaching (98.70%) compared with a pre‐test percentage of (11.5%). This indicates a steep rise in safe practice after the simulation section, a sharp decrease in unsafe practice after the practical section, followed by subsequent decrease in neonatal mortality rate. This paper has been guided by (STROBE, cohort study) checklist. Results The study concluded that the majority of nurses and midwives have some knowledge regarding advanced neonatal resuscitation but still, there is a practice gap because of a shortage of facilities and lack of training, However, training programmes do add value on knowledge and practice for nurses and eventually decrease neonatal mortality rate.